Factors associated with the orthopaedic surgeon's decision to recommend total joint replacement in hip and knee osteoarthritis: an international cross-sectional study of 1905 patients. Issue 10 (October 2018) - Huynh, C.; Puyraimond-Zemmour, D.; Maillefert, J.F.; Conaghan, P.G.; Davis, A.M.; Gunther, K.-P.; Hawker, G.; Hochberg, M.C.; Kloppenburg, M.; Lim, K.; Lohmander, L.S.; Mahomed, N.N.; et al.
Summary: Objective: To determine factors associated with orthopaedic surgeons' decision to recommend total joint replacement (TJR) in people with knee and hip osteoarthritis (OA). Design: Cross-sectional study in eleven countries. For consecutive outpatients with definite hip or knee OA consulting an orthopaedic surgeon, the surgeon's indication of TJR was collected, as well as patients' characteristics including comorbidities and social situation, OA symptom duration, pain, stiffness and function (Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC]), joint-specific quality of life, Osteoarthritis Research Society International (OARSI) joint space narrowing (JSN) radiographic grade (0–4), and surgeons' characteristics. Univariable and multivariable logistic regressions were performed to identify factors associated with the indication of TJR, adjusted by country. Results: In total, 1905 patients were included: mean age was 66.5 (standard deviation [SD], 10.8) years, 1082 (58.0%) were women, mean OA symptom duration was 5.0 (SD 7.0) years. TJR was recommended in 561/1127 (49.8%) knee OA and 542/778 (69.7%) hip OA patients. In multivariable analysis on 516 patients with complete data, the variables associated with TJR indication were radiographic grade (Odds Ratio, OR for one grade increase, for knee and hip OA, respectively: 2.90, 95% confidence interval [1.69–4.97] and 3.30 [2.17–5.03]) and WOMAC total score (OR for 10 points increase: 1.65 [1.32–2.06] and 1.38 [1.15–1.66], respectively). After excluding radiographic grade from the analyses, on 1265 patients, greater WOMAC total score was the main predictor for knee and hip OA; older age was also significant for knee OA. Conclusion: Radiographic severity and patient-reported pain and function play a major role in surgeons' recommendation for TJR.